Efektivitas Media Bola Bersuara dalam Meningkatkan Kemampuan Melempar Bola secara Terarah bagi Penyandang Tunanetra - Suhenda Hermawan; Jon Efendi (Jurnal Penelitian Pendidikan Khusus, 2018)
Background of this study is based on problem finding that found in school. The blind people difficult to search unmove ball because does not sound. Based on the problem above, the aim of this reseach is to find out the effectiveness of sounding ball media to improve  the ability of  throwing ball in righ direction by blind people in PSBN  Tuah Sakato Padang. This reseach was conducted using quasy experiment with one group pretest-posttest design, the data analysis was using Mann Whitney test. The subject of this research are five blind people in PSBN Tuah Sakato Padang. The hypotheses was using t-test, with significant degree 5% (0,005). The result from this research prove that sounding ball is effective to improve  the ability of  throwing ball in righ direction by blind people in PSBN  Tuah Sakato Padang.